Hell's heroes - Shan, Darren (New York : Little Brown and Company, 2010)
Bec, Kernel, and Grubbs gear up for the fight of their lives as the final battle between Earth and the hoardes of the Demonata draws near.
Accelerated Reader AR
Keywords: Demonology -- Juvenile fiction; Magic -- Juvenile fiction; Werewolves -- Juvenile fiction; Horror fiction